1993
DOI: 10.1007/bf00399954
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and impaired glucose tolerance in men and women

Abstract: A follow-up study was carried out to determine whether reduced fetal growth is associated with the development of impaired glucose tolerance in men and women aged 50 years. Standard oral glucose tolerance tests were carried out on 140 men and 126 women born in Preston (Lancashire, UK) between 1935 and 1943, whose size at birth had been measured in detail. Those subjects found to have impaired glucose tolerance or non-insulin-dependent diabetes mellitus had lower birthweight, a smaller head circumference and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
252
4
6

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(280 citation statements)
references
References 11 publications
18
252
4
6
Order By: Relevance
“…On the other hand, the same findings may reconcile this sequence with the more recent observation, that a low birthweight and a lower weight at 1 year predict IGT during the sixth decade of life [9][10][11]. Maternal hyperinsulinaemia is associated with low birthweight, and might represent the trait through which the genetic pressure towards diabetes is routed to the offspring.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, the same findings may reconcile this sequence with the more recent observation, that a low birthweight and a lower weight at 1 year predict IGT during the sixth decade of life [9][10][11]. Maternal hyperinsulinaemia is associated with low birthweight, and might represent the trait through which the genetic pressure towards diabetes is routed to the offspring.…”
Section: Discussionsupporting
confidence: 70%
“…In numerous populations throughout the world, decreased glucose tolerance in adulthood has been associated with low birth weight and thinness at birth (Hales et al, 1991;Phipps et al, 1993;McCance, 1994;Lithell et al, 1996;Fall, 2001a and2001b). A similar observation has been made in pigs by other authors (Poore and Fowden, 2002) but this did not appear to be the case for G1 pigs in the present study during the non-pregnant state.…”
Section: Discussionmentioning
confidence: 99%
“…8 Pre-and postnatal events such as low birth weight or intrauterine growth retardation are thought to influence the health status of adolescents and youth; many population-based studies have reported that low birth weight is predictive of an increased risk for diseases in adulthood such as cardiovascular diseases, type 2 diabetes and hypertension. [9][10][11][12][13] The prevalence of type 2 diabetes has increased among children worldwide during the past decade. Hales, Barker and colleagues 10 hypothesized that low birth weight and reduced growth early in life are strongly linked with impaired glucose tolerance and noninsulin-dependent diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Hales, Barker and colleagues 10 hypothesized that low birth weight and reduced growth early in life are strongly linked with impaired glucose tolerance and noninsulin-dependent diabetes. 10,11 The association between low birth weight in girls and coronary heart disease is thought to reflect the persistence of changes in morphology and physiology that accompany slow fetal growth and seem to be independent of indices of living standards in childhood and adult life. 12,13 Reduced intrauterine growth is linked to high blood pressure (BP), which may explain the association between hypertension and impaired glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%